Women, activism and apartheid South Africa : using play texts to document the herstory of South Africa - Orton, Bev (Emerald Publishing Limited, 2018)
This book investigates women's political activism and conflict in the struggle against apartheid in South Africa, examining issues around domestic violence, racial abuse and women in detention without trial. It builds on the theatrical analysis within play texts such as 'You Strike the Woman, You Strike the Rock' 'Glass House', 'Born in the RSA' 'Has Anyone Seen Zandile?' and 'So What's New?' to chart participation in the struggle against apartheid between 1975 and 1993, providing a political, economic and social herstory of South African women's activism. Further, the focus on play texts addresses the dearth of knowledge of pertinent herstorical moments, women's fight for political agency and equality, how apartheid laws affected women's role in theatre and provides a feminist lens and insight into how these laws affected the herstory of South Africa. The inclusion of a critical perspective from women who wrote plays and worked in theatre takes the book beyond a purely theatrical analysis. It seeks to explore how theatre as a form can help write a 'herstory' of apartheid, not only to document the reality of women's experiences but also as a means to imagine different realities.